Calcium signal propagation in astrocytes - Burrows, Sean (2021)
Astrocytes are glial cells that play many roles in maintaining homeostasis of the central nervous system and modulating both vascular and neuronal networks. Astrocytes express a range of neurotransmitter receptors that allow for communication from the neuron to astrocyte and mediate feedback and modulation of signal transmission at the synapse. Astrocyte calcium signalling caused by receptor activation is responsible for the release of gliotransmitters capable of modulating synaptic activity. The calcium signals of the glia have complex spatiotemporal properties that range from transients, isolated to astrocyte microdomains, to wide intracellular calcium waves capable of propagating within cellular networks. The range that the calcium response covers will determine how many synapses (and blood vessels) could be modulated by feedback from glia. In this study we investigated the factors that control signal propagation in astrocytes using two experimental models: cultured primary astrocytes, and Bergmann glial cells in acutely isolated cerebellar slices.